Food engineering handbook : Food engineering fundamentals / Theodoros Varzakas; Constantina Tzia editor - Tzia, Constantinaeditor
Food Engineering Handbook: Food Process Engineering addresses the basic and applied principles of food engineering methods used in food processing operations around the world. Combining theory with a practical, hands-on approach, this book examines the thermophysical properties and modeling of selected processes such as chilling, freezing, and dehydration. A complement to Food Engineering Handbook: Food Engineering Fundamentals, this text:Discusses size reduction, mixing, emulsion, and encapsulationProvides case studies of solid-liquid and supercritical fluid extractionExplores fermentation